INGLIZ TILINI YUQORI SINF O'QUVCHILARIGA O'QITISHDA TEZ AYTISHLARDAN FOYDALANISHNING PEDAGOGIK AHAMIYATI. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the pedagogical significance of using tongue-twisters in teaching English to upper-grade students. Tongue-twisters are considered an effective phonetic tool that improves pronunciation, phonemic awareness, speech fluency and motivation. The study discusses methods of integrating tongue-twisters into the classroom, provides practical exercises, and highlights their impact on learners’ communicative competence. Recommendations for teachers are offered to help enhance the efficiency of English language instruction.